Youth squad : policing children in the twentieth century - Myers, Tamara, 1964- (McGill-Queen's University Press, 2019)
"In Youth Squad, Tamara Myers chronicles the development of youth consciousness among North American police departments. Starting in the 1930s, urban police forces, from Montreal to New York City to Vancouver, established youth squads and crime prevention programs, dramatically changing the nature of contact between cops and kids. Gone was the beat officer who scared children and threatened youth. In his stead, a new breed of officer - many of them women - emerged whose intentions were explicit: befriend the rising generation. Good intentions, however, produced paradoxical results. Police were late arrivals to the juvenile justice revolution but at midcentury, law enforcement embraced what Myers calls the 'youth turn.' By targeting the environment that gave rise to delinquents and criminals, police aimed for access to children, adolescents, and their cultural spaces, landing youth squads squarely in the oversight and molding of childhood. Police forces intensified their presence in children's lives through juvenile curfew laws, police athletic leagues, traffic safety and anti-corruption campaigns, and school programs. This youth-conscious policing amounted to pervasive supervision and surveillance of young people. Thus, born of a liberal ideal to integrate salvageable working-class youth, mostly boys, into society, the result was to normalize the police presence in childhood. A work at the intersection of juvenile justice, policing and childhood history, Youth Squad illuminates the era between the interwar period -when new solutions to criminal and delinquent behavior were sought - and the punitive turn in the 1970s. Myers demonstrates how the over-policing of young people today is rooted in so-called "child-friendly" schemes of the mid-twentieth-century."--